A New Tool for Calculation of a New Source Code Metric - Stankov, Emil; Gjorgjiev, Kjiro; Madevska Bogdanova, Ana; Jovanov, Mile (FCSE, 2015)
Teaching programming is an activity that becomes more and more popular. Assessment of the students that attend introductory courses in programming can partly be done through presentation of simple source code fragments to them. Students should be able to provide the answer to the question: “What is the output of the given code?” When preparing the code segments, teachers should be aware of the complexity (‘weight’) of the code, and should also try to provide same or similar complexity tasks for all students. Nowadays, when there is a lot of research on the issue of automatic question production, the necessity of having a way to automatically measure the weight of some code is indisputable. In this paper we present a new source code metric that helps defining the weight of the code and a new tool that employs it.